Protein contact dermatitis - case report - Ana Rita Rodrigues Barata; Luis Conde-Salazar (Sociedade Brasileira de Dermatologia, 2013)
Protein contact dermatitis is a skin condition not well known and underdiagnosed by dermatologists, resulting from an IgE-mediated allergic reaction. Clinically it presents as a chronic hand and/or forearms eczema of occupational origin, especially in professionals who work as food handlers. Epicutaneous tests are negative, and to diagnose this condition it is necessary to perform immediate-type allergy tests. The most sensitive and practical is the prick-by-prick test with food that the patient refers to cause intense itching after immediate skin contact. Treatment is symptomatic, and it is mandatory to avoid the responsible allergen, wearing plastic gloves and even sometimes leaving the workplace for symptom resolution.